2007
DOI: 10.1103/physrevb.75.144418
|View full text |Cite
|
Sign up to set email alerts
|

Phase-ordering dynamics in itinerant quantum ferromagnets

Abstract: The phase-ordering dynamics that result from domain coarsening are considered for itinerant quantum ferromagnets. The fluctuation effects that invalidate the Hertz theory of the quantum phase transition also affect the phase ordering. For a quench into the ordered phase a transient regime appears, where the domain growth follows a different power law than in the classical case, and for asymptotically long times the prefactor of the t^{1/2} growth law has an anomalous magnetization dependence. A quench to the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Performing the limit z → 2 in the coefficient in Eq. (16) in front of I 0 , we obtain the result for the exponent given in the main paper:…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Performing the limit z → 2 in the coefficient in Eq. (16) in front of I 0 , we obtain the result for the exponent given in the main paper:…”
mentioning
confidence: 67%
“…Recently, however, many physical systems away from equilibrium were identified which display novel dynamical behavior on intermediate time scales, a behavior often referred to as prethermalization [15][16][17][18][19][20][21][22][23][24][25]. The question arises whether one can expect universality during prethermalization if one drives a system towards a QCP.…”
mentioning
confidence: 99%
“…Quenches, i.e., rapid changes of external parameter values, at T = 0 in both clean and disordered metallic FMs are interesting. Belitz et al (2007) have shown that the coupling of the OP to the fermionic soft modes leads to qualitatively new effects for the late-stage coarsening. Gagel et al (2014) have shown that there is universal pre-asymptotic behavior in general quantum quench problems due to long-range boundary effects.…”
Section: B Open Problemsmentioning
confidence: 99%
“…The reasonable assumption whereby fluctuations within domains should be determined by quantum and thermal fluctuations while the dynamics of interfaces should be close to the ones of their classical counterparts has been demonstrated in some solvable mean-field models [85,86]. A scenario for the time-dependence of a growing length with several crossovers, in the coarsening dynamics of 3d itinerant ferromagnets was put forward in [87].…”
Section: Beyond Physicsmentioning
confidence: 99%